4.5.11Mohamed wrote the paragraph proof to show that ADEG AEFG. What mistake did he make?
ADEG and AEFG are right triangles.
The figure shows DE = EF, AND
EG EG by the Reflexive Property.
Therefore, by the HL theorem,
ADEG AEFG
G
X Х
Choose the correct answer below.
O A. The two triangles are congruent by SAS, not the HL Theorem.
O B. In AEFG, EF is a leg and in ADEG, DE is the hypotenuse, so they cannot be corresponding sides.
O C. The two triangles are congruent by SSS, not the HL Theorem.
OD. In AEFG, EG is a leg, and in ADEG, EG is the hypotenuse, so they cannot be corresponding sides.
4.5.11 Mohamed wrote the paragraph proof to show that ADEG - 1

Answers

Answer 1
Answer:

The two triangles are congruent by SAS, not the HL theorem. Therefore, the correct answer is option A.

Triangle DEG and triangle EFG are right triangles.

The figure shows DE=EF (Given)

EG=EG by the reflexive property.

Therefore, by the HL theorem, Triangle DEG and triangle EFG are congruent.

Here, Mohamed stated postulate wrong.

By SAS postulate, Triangle DEG and triangle EFG are congruent.

Therefore, the correct answer is option A.

To learn more about the congruent theorem visit:

brainly.com/question/24033497.

#SPJ6

Answer 2
Answer:

Answer:B?

Step-by-step explanation:


Related Questions

Mark buys a wooden board that is 9 3/4 feet long. The cost of the board is 0.60 per foot including tax. What is the total cost, in dollars of marks board
What is the ratio 7 to 12 as a fraction in simplest form?
$0.63 + _______ = $1.00
Wyatt uses 3.15 cups of flour in a recipe that makes 9 shortcakes Cora uses 2.4 cups of flour in a recipe that make 8 shortcakes how much more flour per shortcake is needed for Cora’s recipe
2. How many solutions does this system have? 2x + y = 3, 6x = 9 – 3yA) 1B) NoneC) InfiniteD) 2

Two equations are given below:a − 3b = 16
a = b − 2

What is the solution to the set of equations in the form (a, b)?

(−2, −6)

(−7, −9)

(−11, −9)

(−12, −10)

Answers

\left \{ {{a - 3b = 16} \atop {a = b - 2}} \right. \n \n \left \{ {{a = 16 + 3b} \atop { 16 + 3b = b - 2}} \right. \n \n \left \{ {{a = 16 + 3b} \atop {3b - b = - 2 - 16}} \right. \n \n \left \{ {{a =16 + 3b} \atop {2b = -18}} \right. \n \n \left \{ {{a=16 + 3b} \atop {b=-9}} \right. \n \n \left \{ {{a=16 + 3b = 16 + 3*(-9) = 16 - 27 = -11} \atop {b=-9}} \right.

Answer a = -11, b = -9

Answer:

third one

Step-by-step explanation:

What is 12 miles below sea level

Answers

Answer:

I'm assuming you mean the negative number of it so -12

Step-by-step explanation:

Answer:

-12 miles

Step-by-step explanation:

below is a key word, so you know you are going down

Mike went to the store to buy shirts. The shirts were $45 each. The store was offering the following discount Mike decided to buy 3 shirts. Not including sales tax, how much money did Mike save by buying the shirts at the discounted price?

Answers

Mike saves $36 by buying the shirts at a discounted price.

What is the percentage?

The percentage is defined as a given amount in every hundred. It is a fraction with 100 as the denominator percentage is represented by the one symbol %.

The percentage is also called the indicating hundredths. Thus, 2% is two-hundredth, which means 2%=2/100=0.02.

Given the offer,

By 1 at regular price ($45) and get 40% off on two shirt

40 % of 45 ⇒ 0.40 × 45 = $18

So shirt price = 45 - 18 = $27/each

Since 2 shirt buy at this price = 2 × 27 = $54

Money saved = 2×45 - 54 = $36

Hence "Mike saves $36 by buying the shirts at a discounted price".

For more about the percentage,

brainly.com/question/13450942

#SPJ6

Given question is incomplete complete question is ;

Answer:

54

Step-by-step explanation:

multiplying polynomials

find the product

(2a-1)(8a-5)

Answers

The product of (2a-1)(8a-5) is 16a² - 18a + 5.

To find the product of (2a-1)(8a-5), we can use the distributiveproperty. This means that we multiply each term in the first polynomial (2a-1) by each term in the second polynomial (8a-5) and then combine like terms.

Applying the distributive property, we have:

(2a-1)(8a-5) = 2a(8a) + 2a(-5) - 1(8a) - 1(-5)

Simplifying this expression, we get:

16a² - 10a - 8a + 5

Combining liketerms, we have:

16a² - 18a + 5

Therefore, the product of (2a-1)(8a-5) is 16a² - 18a + 5.

In this case, we multiplied each term of the first polynomial by each term of the second polynomial, resulting in four terms. Then, we combined like terms to simplify the expression. The final product is a quadratic polynomial with a leading coefficient of 16 and terms involving the variable 'a'.

To learn more about Polynomials;

brainly.com/question/11536910

#SPJ6

(2a - 1) (8a - 5)

= {2a(8a - 5)} - {1(8a - 5)}

= 16a² - 10a - 8a + 5

= 16a² - 18a + 5

The length of the base of a right-angled triangle ABC is 6 centimeters and the length of the hypotenuse is 10 centimeters. Find the area of the triangle.

Answers

Answer:

24

Step-by-step explanation:

Ok, so we see that we have 6 as a leg of the right triangle and 10 as the hypotenuse.  As we look closer, we can tell that this makes the Pythagorean triple 6, 8, 10.  6, 8, 10 is just the Pythagorean triple 3, 4, 5 but it is multiplied by 2.  So now that we know both the legs of this right triangle, we can use the area of a triangle formula (bh)/2.  6*8=48 and 48/2 = 24 which gives us our answer.

If f(x) = 3x2 – 4 and g(x) = 2x – 6, what is g(f(2))?
O-16
o -2
O 8
0 10

Answers

Answer:

The last option, 10 is correct

Step-by-step explanation:

f(x) = 3x^2 - 4

f(2) = 3(2)^2 - 4

f(2) = 12 - 4

f(2) = 8

g(x) = 2x - 6

g(8) = 2(8) - 6

g(8) = 16 - 6

g(8) = 10

This means that g(f(2)) is equal to 10

Answer:

Its 10 or D

Step-by-step explanation: